Analisis Sistem Informasi Akutansi Arus Kas pada PT. Pusat Kreatif Indonesia - Nindia Febrianti, Poppy; Wartini; Triyaningsih, Lulus (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Cash flow analysis is also useful for evaluating a company's financial performance and identifying potential problems or opportunities. This study aims to describe cash flow in helping to improve the effectiveness of fund management at PT. Pusat Kreatif Indonesia. The study was conducted during working hours starting from 08.00-15.00 every Monday - Friday at PT Pusat Kreatif Indonesia on Jl. Danau Toba 70B, Tegal Gede - Sumbersari Jember. Analysis of the cash flow report ratio used by researchers to measure the effectiveness of PT's cash flow performance. Pusat Kreatif Indonesia. After analyzing the company's financial report performance measurement, it can be seen that the cash flow ratio of PT. Pusat Kreatif Indonesia during 2023 to September fluctuated. This can be seen where the cash flow report ratio analysis. The level of liquidity owned by PT. Pusat Kreatif Indonesia can be said to be in an effective state. This is supported by an increase in sales which results in an increase in cash in operational cash flow. So that the company is able to meet all its current obligations. The level of financial flexibility of PT. Pusat Kreatif Indonesia when measured from free net cash flow shows that the free cash in the company is sufficient to make investments. Because this company is able to spend capital for office needs.